2020
DOI: 10.1002/mnfr.201900912
|View full text |Cite
|
Sign up to set email alerts
|

Use of Physiologically Based Kinetic Modeling to Predict Rat Gut Microbial Metabolism of the Isoflavone Daidzein to S‐Equol and Its Consequences for ERα Activation

Abstract: Scope To predict gut microbial metabolism of xenobiotics and the resulting plasma concentrations of metabolites formed, an in vitro–in silico‐based testing strategy is developed using the isoflavone daidzein and its gut microbial metabolite S‐equol as model compounds. Methods and results Anaerobic rat fecal incubations are optimized and performed to derive the apparent maximum velocities (Vmax) and Michaelis–Menten constants (Km) for gut microbial conversion of daidzein to dihydrodaidzein, S‐equol, and O‐desme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 91 publications
(150 reference statements)
2
30
0
Order By: Relevance
“…The importance of taking differences kinetics into account when defining relative potencies of PAs was previously shown to also hold for the PAs themselves for which substantial differences in clearance may exist (Lester et al 2019). Successful incorporation of intestinal microbiota in PBK models has been demonstrated so far in only a few other studies (Mendez-Catala et al 2020;Wang et al 2020) and the current study provides another proof-of-principle for this approach.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The importance of taking differences kinetics into account when defining relative potencies of PAs was previously shown to also hold for the PAs themselves for which substantial differences in clearance may exist (Lester et al 2019). Successful incorporation of intestinal microbiota in PBK models has been demonstrated so far in only a few other studies (Mendez-Catala et al 2020;Wang et al 2020) and the current study provides another proof-of-principle for this approach.…”
Section: Discussionmentioning
confidence: 54%
“…The conditions for anaerobic rat fecal incubations with riddelliine N-oxide were optimized with respect to linearity in time and with respect to the amount of fecal sample as previously described (Wang et al 2020;Yang et al 2019). Using the optimized linear conditions, the riddelliine N-oxide 1 REP values for riddelliine N-oxide relative to riddelliine as derived based on literature data a A dose correction was performed for the data reported by Wang et al (2005) and Chou et al (2003), since these studies did not apply equimolar dose levels.…”
Section: Anaerobic Rat Fecal Incubationsmentioning
confidence: 99%
“…The bacterial communities in colon and feces have been reported to be highly comparable [ [38] , [39] , [40] ]. Furthermore, proofs of principle that show that anaerobic in vitro incubations using fecal communities can be used to predict intestinal microbial metabolic activities have been reported [ 41 ], supporting the use of anaerobic fecal samples as a representative population of intestinal microbes. Therefore, the use of anaerobic fecal samples for the study of intestinal microbial metabolism represents a first tier approach to estimate its contribution to the total metabolism in the host.…”
Section: Discussionmentioning
confidence: 99%
“…However, the colon, harboring 70% of the total bacteria present in the gut, is the main site for bacterial fermentation. [24] Furthermore, it has been shown that the bacterial communities in colon and feces are highly comparable. [25][26][27] In addition, proofs of principle have shown that anaerobic in vitro incubations using fecal communities can be used to predict intestinal microbial metabolic activities, [24] supporting the use of anaerobic fecal samples as a representative population of intestinal microbes.…”
Section: Discussionmentioning
confidence: 99%